2014
DOI: 10.1136/tobaccocontrol-2013-051502
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the emergence of the tobacco industry's use of the term tobacco harm reduction in order to inform public health policy

Abstract: ObjectivesTo explore the history of transnational tobacco companies’ use of the term, approach to and perceived benefits of ‘harm reduction’.MethodsAnalysis of internal tobacco industry documents, contemporary tobacco industry literature and 6 semistructured interviews.ResultsThe 2001 Institute of Medicine report on tobacco harm reduction appears to have been pivotal in shaping industry discourse. Documents suggest British American Tobacco and Philip Morris International adopted the term ‘harm reduction’ from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 25 publications
1
88
0
2
Order By: Relevance
“…Givel (2011) analyzed 99 Federal tobacco policy documents spanning 2004-2008, during which Phillip Morrisat odds with other major tobacco companies -began supporting legislation (the eventual FSPTCA) embodying tobacco harm reduction. Both studies conclude the term harm reduction was used disingenuously by the tobacco industry to rehabilitate their public image, regain access to policymakers, and ensure profits (Givel, 2011;Peeters & Gilmore, 2014).…”
Section: Tobacco In Us Newsprintmentioning
confidence: 94%
See 4 more Smart Citations
“…Givel (2011) analyzed 99 Federal tobacco policy documents spanning 2004-2008, during which Phillip Morrisat odds with other major tobacco companies -began supporting legislation (the eventual FSPTCA) embodying tobacco harm reduction. Both studies conclude the term harm reduction was used disingenuously by the tobacco industry to rehabilitate their public image, regain access to policymakers, and ensure profits (Givel, 2011;Peeters & Gilmore, 2014).…”
Section: Tobacco In Us Newsprintmentioning
confidence: 94%
“…Two additional studies examined harm reduction within tobacco industry documents, casting skepticism toward the sincerity of tobacco companies (Givel, 2011;Peeters & Gilmore, 2014). Peeters and Gilmore (2014) analyzed 455 litigation documents from four tobacco transnational companies spanning 1971-2009, and found that the phrase "harm reduction" entered the industry vernacular in 1999 and began to be used publically in 2002 following an influential report published by the Institute of Medicine.…”
Section: Tobacco In Us Newsprintmentioning
confidence: 98%
See 3 more Smart Citations